Design, development, and public health: Conceptualizing health and wellness strategies for multifamily projects through a private development lens - Rider, Traci Rose; van Bakergem, Margaret; Park, Jinoh; Wang, Xi; Hipp, J. Aaron (Enquiry The ARCC Journal for Architectural Research, 2018)
As awareness of the built environment's impact on individual and community health spreads through design and construction, different stakeholders are engaging in conversations of strategies and metrics. This paper explores the structure, methodology, and findings of research supported by the Robert Wood Johnson Foundation addressing how multifamily developers conceptualize, discuss and implement health strategies in their projects. Framed in a Critical Theory perspective, this research first explores the traditional multifamily development decision-making process, specifically targeting how early adopters in multifamily development are discussing health and wellness in their projects. By unpacking the discussions around health and wellbeing in design, real estate development, and public health, aligned concepts are identified to operationalize these concepts for further exploration. Using a comparative case study strategy addressing how and why (Yin 2017), five developers positioned as early adopters were engaged to better understand how they each conceptualize, implement and measure health strategies in their multifamily projects. Two-day in-depth interviews were held in two initial developers' home offices, addressing their standard design and decision-making processes and evolving into specific consideration of various health strategies. Four additional developers were engaged either over the phone or in person. Interview protocol ensured that discussion topics were standardized at the outset, with the following topics addressed with each partner: (1) company mission, (2) organizational structure, (3) differentiation in the market, (4) company evaluation metrics, (5) assessment scales, (6) decision-making processes, (7) market trends, (8) use of evidence-based data, (9) internal health discussions, and (10) investor relationships. Cyclical data collection, transcription, and analysis allowed the interview protocol to be modified for emergent topics. Site visits, website analysis, and clicks through national online real estate databases also contributed to a holistic perspective of this complex problem. Findings indicate that multifamily developers are focusing on upfront, marketable strategies that are likely to foster mental and social health, but with little regard of applying any form of evaluative metrics. Rating systems addressing health are of little help. When asked directly about choices to influence the health of residents, participants heavily cited (1) location, emphasizing access to community amenities; (2) place making, for community building and social and mental wellbeing; and (3) physical fitness opportunities through fitness spaces. Even those developers viewed as early adopters are uncomfortable discussing health strategies using a public health lens. This research intends to highlight interdisciplinary conversations surrounding health in multifamily real estate, contributing to more rigorous adoption of health strategies in this challenging building type. These findings can be valuable to stakeholders in design, development, private investment, property management, public health, community design, and policy.